The Influence of Human Development, Institutional Quality and ?ISIS Emergence on Foreign Direct Investment in Iraq ? - Zeravan Abdulmuhsen Asaad; Bayar MohamedRasheed Marane (Technium Social Sciences Journal, 2020)
This study investigates the influence of human development and institutional quality on the foreign direct investment net inflows on the gross domestic product in Iraq for the period (2004-2016) by using OLS regression. The empirical results show that governance sub-indicators do not actually matter much in attracting Foreign Direct Investment (FDI) inflows in Iraq. This variable shows fixed results with a different sign; the Political Stability (PS), Government Effectiveness (GE) and Rule of Law (RL) are the sub-indicators of the governance with a positive sign which is insignificant, while the Voice and Accountability (VA), Regulatory Quality (RQ) and Control of Corruption (CC) are the sub-indicators of the governance index with a negative sign and an insignificant impact on FDI inflows. The value of Worldwide Governance Indicators (WGI) coefficient is negative and significant at 10% level. Hence it has been concluded that the explanatory variables are negatively associated with the dependent variable FDI. In contrast, the Human Development Index (HDI) has a positive and significant impact on FDI inflows. This study found that Islamic State of Iraq and Syria (ISIS) emergence after (2013) had a significant coefficient, meaning that ISIS has affected the level of FDI inflows.